Abnormal Returns Related to Credit Rating Downgrades : Empirical Evidence from the Nordic Markets 2001–2018 - Mäkinen, Mira (My University, 2019)
Previous studies from the U.S. show, that markets tend to react more to negative news than to the positive ones. This theory applies to credit rating downgrade announcements, which have typically caused negative abnormal returns both on the short and the long-term after the announcement. The stock returns after credit rating downgrades however have not been widely tested in smaller markets, such as in the Nordic countries. Therefore, the aim of this study is to examine the stock returns reaction of companies listed in the Nordic countries around the time when the credit rating downgrade is announced. A typical method to study whether credit rating downgrades have an impact to stock returns is the event study method, followed by a regression analysis. The results of the event study suggests that the credit rating downgrades are connected with abnormal stock returns in the Nordic markets. However, the statistically significant negative abnormal returns occur mostly prior to the actual event date indicating that the negative abnormal returns are not caused by the credit rating downgrades. This can be due to the deteriorated financial conditions of the rated company being noted by markets before the actual credit rating actions take place and the downgrade announcement is published. Also, other announcements on the markers can cause negative abnormal returns in the event window before the downgrade. Based on the results of this study the investors react more negatively to the downgrades of companies in the investment grade than in the speculative grade. Also, the negative reaction is stronger, when a downgrade causes the rated company to fall from the investment grade to the speculative grade. Negative credit watch listings and negative outlooks announced prior to the credit rating downgrade however effect positively to the abnormal returns around the event date.